Variabilidade genética e associação entre caracteres agronômicos, fisiológicos e fitoquímicos em variedades de Artemisia annua L - Bolina, Cristiane de Oliveira (2011)
Artemisia annua L. (Asteraceae) is a highly aromatic annual herb, native from Asia and acclimated in Brazil. The leaves are a rich source of artemisinin, a sesquiterpene lactone used in the preparation of drugs for the treatment of malaria, and also of essential oil used in cosmetics and hygienic products. This study aimed to estimate the genetic variability and correlation between agronomic, physiological and phytochemicals traits in varieties of A. annua, also to characterize the content, yield and essential oil composition. The design was completely randomized and treatments were the varieties Artemis, 2/39x5x3M and 2/39x1V of A. annua, submitted to agronomic, physiological and phytochemical evaluations. For the accomplishment of the genetic distance estimates dissimilarity matrices had been generated using the Euclidean distance and Tocher’s and UPGMA’s grouping methods. Moreover, relative importance of the characters for genetic divergence for the method of Singh was evaluated. The relationship between the studied characters was estimated using Pearson’s correlation coefficient and the significance level was analyzed by test t. The analyses were performed in the Genes software and the dendrograms obtained from the NTSYS program. The separation and quantification of substances present in the essential oil were performed by gas chromatography with flame ionization detector and the identification of them were made in a gas chromatography coupled with mass spectrometer. Tocher’s and UPGMA’s methods agreed among themselves in the formation of groups and the presence of genetic variability within varieties allowed the identification of dissimilar individuals with high average for all traits. The number of branches, the intracellular concentration of CO2 and oil yield were the traits that contribuited most to the genetic dissimilarity of A. annua. The accesses B24, C5 and C32 were the most promising within populations and must be conserved for future crossings, and the most promising crosses for obtaining desired segregant populations B24 x C5, B24 x C32 e C5 x C32. Correlation met positive and significant between canopy volume of characters and essential oil yield in the variety 2/39x5x3M, however, this correlation was not found in the variety 2/39x1V. In both varieties, there was a negative and significant correlation between canopy volume and content of artemisinin. The variety 2/39x1V produced the greatest dry mass of leaves and consequently achieved the highest level and the highest yield of essential oil. Camphor, ymuuroleno and 1.8 cineole were the compounds found in higher concentrations in the essential oil of varieties 2/39x5x3M and 2/39x1V of A. annua.